PENAMPILAN PERTUMBUHANDAN HASIL DUA BELAS GENOTIPE GANDUM (Triticum aestivum L.) DITANAM di DATARAN RENDAH DALAM RANGKA MENCARI CALON TETUA ADAPTIF DATARAN RENDAH - Yosep Chandra Puspita; Nugraheni Widyawati; Djoko Murdono (Agric, 2013)
In order to looking for some parent materials of wheat adaptif tropical lowland, there have been done an experimental field to study the phenotype of twelve wheat genotype (Triticum aestivum L.) that cultivated in lowland from June 17, until October 17, 2011, at a field of PT. Sango Ceramics Indonesia, Mangkang -Wonosari, Ngalian, Semarang, Central of Java, about 13 meter above the sea level. The purpose of these research were to observe the phenotype performance of twelve wheat genotypes at tropical lowland and to determine the wheat genotype that are potential to be observe as parent materials which adaptif in tropical lowland. The research used Randomized Block Design with twelve treatments and three replications. The treatments were 1) OASIS/SKAUZ//4*BCN, 2) HP 1744, 3) LAJ3302/MO88, 4) RABE/MO88, 5) H-21, 6) G-21, 7) G-18, 8) Menemen, 9) Basribey, 10) Alibey, 11) Selayar and 12) Dewata. The result of this research were the growth and yield performance of twelve wheat genotypes at tropical lowland 13 m above the sea level were different in crop height, number of tiller, 1000 grain weight, number of grain/spikelet, grain weight of forth line but there werenot different in flowering time, harvest time and one liter weight of grain. The wheat genotypes that are potential performance to be observed as parent materials of tolerant lowland wheat are Basribey and Menemen genotype.